(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This article analyzes the definitions of micro-story and minifiction in order to recount their contributions, while proposing a review of the history of gender to expand their studies and present another line of research, which includes its aesthetic principles to account for the artistic and social function they have inside the literary tradition. At the same time, it allows us to reflect on what we consider as a “story” today, given that the minifiction is distinguished by admitting devoid narration texts, even without a textual support.